TARGETING L2 WRITING PROFICIENCIES: INSTRUCTION AND AREAS OF CHANGE IN STUDENTS’ WRITING OVER TIME - Archibald, Alasdair (International Journal of English Studies, 2001)
Writing in a second language is a complex activity requiring proficiency in a number of different areas. l Writing programmes often focus on particular areas of skill and knowledge that are seen as important to the overall process. This study looks at the effects of the focus of teaching on student writing. Fifty students on an eight-week pre-sessional programme were asked to write a 250-word assignment at the start and the end of their courses. These were graded on a nineband scale using a seven-trait multiple-trait scoring system. The results show that discourse organisation and argumentation, which were the primary focus of classroom study, improved more than other areas. This suggests that tutors should look at writing proficiency in terms of an overall balance of proficiencies and that targeting aspects of student writing can affect this overall balance.